Service Level Agreement (SLA) for Cloud Computing Compilation with Common and New Formats (International Journal of Scientific Research and Management (IJSRM), 2018)
Future fit demand and flexible solutions combined with high quality of services that is what latest information technology by cloud computing stands for. In the last couple of years, many scientists and researchers have improved computing systems that result in it more users’ friendly day by day from all perspectives. Nowadays, computing system promises to fulfill maximum outcome using minimum efforts or resources from user’s point of view, and it comes from overcoming several technological eras like cluster computing, grid computing, etc. It is obvious that as more the technology advances, the complexity also increases in terms of privacy, security, and service quality. Recently business applications want services being delivered instantly. Pay-as-you-go is the latest trend for most of the business applications and to suit it precisely a process should be followed which might be the Service Level Agreement (SLA). In this paper, we started with defining cloud computing and how it defers from traditional computing system. We also compile the format and parameters of estimating SLA for cloud computing in order to be benefited maximum from it in terms of users’ as well as providers’ perspective